(untitled) (Yangi O’zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2024)
Proverbs and sayings are more than just witty rhymes and catchy phrases. They are windows into the soul of a culture, offering nuggets of wisdom gleaned from generations of experience. Comparing English and Uzbek proverbs reveals fascinating parallels and divergences, reflecting the unique histories and values of each people. Both English and Uzbek proverbs emphasize the importance of hard work and perseverance. "A rolling stone gathers no moss" finds its Uzbek counterpart in "Taqiyon tosh suv yiymaydi" (A spinning stone doesn’t drink water). Similarly, the value of patience is enshrined in both cultures: "Rome wasn’t built in a day" echoes the Uzbek saying "Tomchi tomchi ko’l bo’lar" (Drops by drop a lake forms).Both languages highlight the significance of family and community. "Blood is thicker than water" resonates with the Uzbek proverb "Uka uka o’g’ri bo’lsa ham bir-birini tashlamaydi" (Even if brothers become thieves, they won’t abandon each other). The importance of hospitality is also shared: "The guest is always right" finds its Uzbek counterpart in "Mehmon Xudo mehmoni" (The guest is a guest of God).However, comparisons reveal intriguing differences too. English proverbs often reflect a pragmatic, individualistic spirit. "Every man for himself" stands in contrast to the Uzbek saying "Yolg’iz o’yin - to’y emas" (A solo game is not a wedding) highlighting the importance of communal joy Uzbek proverbs often emphasize respect for elders and tradition. "Oq soqollilarning kalomi – oltindir" (The word of the white-bearded is gold) embodies this reverence, while "Qadimga qarshi yangi - yangidir" (What is new against the old is new) suggests a balance between embracing innovation and honoring tradition.